THE INFLUENCE OF EMPLOYEE ENGAGEMENT, EMPLOYEE JOB SATISFACTION, INNOVATIVE WORK BEHAVIOR ON THE ORGANIZATIONAL RESILIENCE OF PT MITSUBISHI - Fidella Wijayanti Kurniawan; Muhammad Richo Rianto (Draf Solusi Indonesia, 2023)
The influence of employee involvement, employeejob satisfaction and innovative work behavior on theobject of this research aims to find out how muchinfluence employee involvement (X1), employee jobsatisfaction (X2), innovative work behavior (X3) hason the organizational resilience (Y) of PT Mitsubishi.In an increasingly difficult situation, PT Mitsubishi is acar company that is famous for its strong engines,good and luxurious models so that it can attractcustomers. PT Mitsubishi has employee involvement,employee job satisfaction and innovative workbehavior aimed at retaining customers and increasingsales results obtained from employees to attractcustomers so that the company will experience anincrease or decrease